geoMorphology and stratigraphy area river basin Mishca (canary district, province of víctor faJardo, ayacucho departMent) - Castañeda, Marko (2014)
Headwaters of Mishca River in Canarias District, Province of Victor Fajardo in Ayacucho, are morphologically located in the zone of Interandean Valleys and geologically is on the western side of Eastern Cordillera and local litostratigraphy ages ranges between Paleozoic and Mesozoic corresponding to the units Mitu (Upper Permian-Triassic) and Pucara (Upper Triassic-Lower Jurassic) Groups and Chunumayo Formation (Middle Jurassic). Igneous rocks are defined as part of Querobamba Granitic Complex, formed during Upper Paleozoic Magmatic Cycle. Local stratigraphy is covered discordantly by recent unconsolidated Quaternary sediments.